2022
DOI: 10.3390/ijms23137023
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Regulated Cell Death Responses in Viral Infections

Abstract: The fate of a viral infection in the host begins with various types of cellular responses, such as abortive, productive, latent, and destructive infections. Apoptosis, necroptosis, and pyroptosis are the three major types of regulated cell death mechanisms that play critical roles in viral infection response. Cell shrinkage, nuclear condensation, bleb formation, and retained membrane integrity are all signs of osmotic imbalance-driven cytoplasmic swelling and early membrane damage in necroptosis and pyroptosis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 276 publications
0
11
0
Order By: Relevance
“…For instance, the ability to delay or prevent apoptosis provides viruses with more time and opportunities to replicate and assemble viral particles and promotes long-term survival of viruses in the host cell as well as their spread to surrounding hosts cells, which can lead to persistent infection. Thus, apoptosis induced by HIV-1 contributes, among many mechanisms, to the gradual T cell decline that occurs in HIV-infected patients, and programmed cell death of uninfected bystander T lymphocytes, including CD4 + and CD8 + T cells ( Rex et al 2022 ). The same is true for cellular senescence, often considered a part of the host cell response to fight viruses ( Baz-Martínez et al 2016 ; Kelley et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ability to delay or prevent apoptosis provides viruses with more time and opportunities to replicate and assemble viral particles and promotes long-term survival of viruses in the host cell as well as their spread to surrounding hosts cells, which can lead to persistent infection. Thus, apoptosis induced by HIV-1 contributes, among many mechanisms, to the gradual T cell decline that occurs in HIV-infected patients, and programmed cell death of uninfected bystander T lymphocytes, including CD4 + and CD8 + T cells ( Rex et al 2022 ). The same is true for cellular senescence, often considered a part of the host cell response to fight viruses ( Baz-Martínez et al 2016 ; Kelley et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia may be caused by cell-in-cell (CIC) structures, which are phenomena referring to lymphocytes internalized in IECs [ 41 , 120 , 137 ]. CIC structures, commonly found in cancer, can be driven by mitosis and potentially tumor-induced autophagy [ 138 ]. Interestingly, lymphopenia has been associated with mitochondrial dysfunction [ 139 ].…”
Section: Microbial Translocationmentioning
confidence: 99%
“…Apoptosis, as well as two forms of regulated necrosis—necroptosis and pyroptosis, are considered as the main ways of virus associated cell death [ 28 , 29 ]. cfDNA can also originate from neutrophil extracellular traps (NETs), web-like structures formed due to the programmed death of neutrophils called NETosis in response to infections or cancer [ 30 ]. Brinkmann et al [ 31 ] for the first time reported that NETs are composed of decondensed chromatin complexed with neutrophil proteins (e.g., neutrophil elastase and myeloperoxidase) which are able to capture, neutralize, and kill microbes.…”
Section: Brief Overview Of Cell-free Dnamentioning
confidence: 99%